Implementación de una unidad motor generador ac-ac, para realizar prácticas demostrativas de la puesta en paralelo entre dos unidades de generación ac, en el laboratorio de máquinas eléctricas de la Universidad Técnica de Cotopaxi /^cSegundo Hernán Acosta Gutiérrez y Juan Rolando Velasco Chimba - Acosta Gutiérrez, Segundo Hernán (2013)
The teaching-learning process of technical careers implies the interaction of theory with practice, for this reason the electrical machine laboratory was implemented with a motor-generator unit, the purpose of this implementation is to have a team that allows laboratory experiments to be carried out in independently and connect in parallel with other power generation units that have similar parameters. This motor-generator group is also implemented with advanced technology equipment, which automatically controls its parameters in the face of a variable electrical load. A very important characteristic of this equipment is the facility to experience electrical load transfers between AC generators and also to experience the behavior of generators in the face of rapid variations in electrical load. Other important characteristics of this equipment is that it has digital measurement equipment and its rotor speed controls and voltage supply to the field winding are automatic, we must highlight the speed control with which it is implemented, which indirectly and automatically controls The rotation of the generator, controlling the speed and torque of the primary machine, this control is done without electrical feedback from the generator. The presentation of this project is divided into three chapters, described as follows: In the first chapter an introduction to synchronous and asynchronous electrical machines is compiled, it also describes the necessary conditions for the connection and distribution of load, between synchronous generators connected in parallel It also contains the control of voltage and reactive power in electrical systems. The second chapter contains the type, methods and research techniques used in the development of this project and the results are interpreted by means of the analysis of the graphs obtained, it also contains the conclusions and recommendations of this work. The third chapter is a description of all the elements used to implement the AC - AC motor generator unit, it also contains the laboratory guides and the Operation Manual.